Implementasi Real-Time Dynamics Lighting dan Soft Shadow pada Lingkungan Game 2-Dimensi (Studi Kasus Game Wipe-It-Off) - Muhammad Dikri Robinsyah; Eriq Muhammad Adams Jonemaro; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The growth of the gaming industry started from the development of 2-dimensional games. But in its development, 2-dimensional game began to lose with 3-dimensional game. While 2-dimensional games have the advantages i.e. the development cost is cheaper and the development time is shorter than the 3-dimensional game. Adding real-time dynamics lighting and soft shadow methods is expected to increase the value of the two-dimensional game itself. Therefore in this project is implemented by the method in 2-dimensional game environment with case study of Game Wipe-It-Off. Real-time dynamics lighting and soft shadow methods are implemented using OpenGL Graphic API, C ++ Language, and GLSL. From performance testing obtained information about frame rate, frame time, CPU usage, and memory usage in game using method and not using method has not significant difference. So it does not affect much the performance of the game. Therefore the use of such methods is highly recommended to add value of the game without having to sacrifice game performance. In addition, the implementation of the method there is no indication of a memory leak, where the use of memory has a stable value with the difference between the largest and the smallest memory usage is 790528 bytes.